Cost-minimization analysis of degludec/liraglutide versus glargine/aspart: economic implications of the DUAL VII study outcomes - Torre E; Bruno GM; Di Matteo S; Martinotti C; Oselin M; Valentino MC; Parodi A; Bottaro LC; Colombo GL (Dove Medical Press, 2018)
Enrico Torre,1 Giacomo Matteo Bruno,2 Sergio Di Matteo,2 Chiara Martinotti,2 Martina Oselin,2 Maria Chiara Valentino,2 Alessio Parodi,3 Luigi Carlo Bottaro,4 Giorgio Lorenzo Colombo5 1Endocrinology, Diabetology and Metabolic Diseases Unit, ASL3, Genoa, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche S.r.l., Health Economics & Outcomes Research, Milan, Italy; 3General Direction International Evangelic Hospital, Genoa, Italy; 4General Direction, ASL3, Genoa, Italy; 5Department of Drug Sciences, University of Pavia, Pavia, Italy Background: Diabetes represents a relevant public health problem worldwide due to its increasing prevalence and socioeconomic burden. There is no doubt that tight glycemic control reduces the development of diabetic complications such as the long-term costs related to the disease. The aim of our model was to calculate total direct costs associated with the two treatments considered in DUAL VII study, and hence evaluate the potential economic benefits for the National Health System (NHS) deriving from the use of insulin degludec plus liraglutide (IDegLira) in a once-daily fixed combination. Materials and methods: We applied the cost-minimization technique adopting the NHS point of view to the DUAL VII trial outcomes. In the model, developed in Microsoft Excel®, we calculated and compared annual costs per patient of the two therapeutic options for type 2 diabetes (T2D) patients not achieving glycemic control on basal insulin and metformin described in the trial, including costs of therapy management and side effects, both negative and positive. Annual treatment costs were calculated based on IDegLira and basal bolus end-of-trial doses resulting in a 1:2 ratio (40.4 U vs 84.1 U). Therefore, maintaining the IDegLira/basal bolus at 1:2 dose ratio, we calculated the correlation between the dose reduction and costs compared to DUAL VII doses base case scenario. Results: Total treatment costs were obtained by adding annual cost of drug, needles, glycemic self-monitoring, hypoglycemic events, and effect on consumption of other drugs. Total annual costs of IDegLira combination resulted in €434 higher than basal bolus in DUAL VII base case (40.4 U); the two treatments reported equal costs at 34% dose reduction (26.7 U), while below this value IDegLira treatment became less expensive, with about €215 gain at 50% dose reduction (20.2 U). It is also important to notice that above the break-even point, until an IDegLira dose of 30 U, the cost difference is negligible in view of the clinical benefit provided by the fixed combination highlighted in DUAL VII trial. Conclusion: Adding the significant clinical findings derived from DUAL VII trial to our economic evaluation, IDegLira seems to offer an important alternative to basal-bolus therapy. Keywords: diabetes, cost minimization, IDegLira, basal-bolus therapy